2018
DOI: 10.18272/aci.v10i1.959
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Serotype Differences in Urban and Semi-rural Communities in Ecuador

Abstract: Dengue is a major vector-borne infection causing large outbreaks in urban communities in tropical regions. During the period 2010- 2014; 434 serum samples from febrile patients were collected from a  semi-rural community hospital located in the norwestern region of Ecuador. Dengue virus (DENV) was investigated by reverse transcriptase PCR; a total of 48 samples were positive for dengue. During our study we detected  DENV-2 and DENV-3 from 2010 to 2013 and the four  DENV  serotypes during the period 2013-2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…For DENV-2, the presence of the Asian-American genotype in the sequences from Norte de Santander was corroborated, and these results were consistent with those reported in recent years in the region [9,49], and this genotype replaced the American genotype since the early 1990s [9], resulting in an increased number of serious cases in Colombia and throughout America [51]. However, it has been observed that this genotype has evolved thereafter, and evidence on the co-circulation of different clades/lineages has been reported in the country [9].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…For DENV-2, the presence of the Asian-American genotype in the sequences from Norte de Santander was corroborated, and these results were consistent with those reported in recent years in the region [9,49], and this genotype replaced the American genotype since the early 1990s [9], resulting in an increased number of serious cases in Colombia and throughout America [51]. However, it has been observed that this genotype has evolved thereafter, and evidence on the co-circulation of different clades/lineages has been reported in the country [9].…”
Section: Plos Onesupporting
confidence: 90%
“…It is important to highlight the fact that two Colombian DENV-1 sequences obtained during 2015-2016 were grouped with a set of sequences from the southern coast of Ecuador collected during 2014 [47] and Panama (with a bootstrap value of >75%), suggesting a close genetic relationship between the viruses circulating between Colombia and Ecuador and between Colombia and Panama, further supporting the notion that the DENV flow can occur commonly among countries owing to their proximity [48][49][50].…”
Section: Discussionmentioning
confidence: 67%
“…These changes may have driven the uptick in DENV FoI in Esmeraldas and the Amazon, which were not previously considered high risk areas. In Esmeraldas, connectivity first increased with Colombia, consistent with the observation that the DENV serotypes circulating in Esmeraldas between 2010–2014 more closely matched those circulating in Colombia than the rest of Ecuador [ 34 , 36 , 62 ]. A more recent study demonstrated dissemination of DENV1 and DENV2 from urban centers to more isolated communities in the Esmeraldas province [ 36 ].…”
Section: Discussionsupporting
confidence: 77%
“…As previously low-population rural areas become increasingly urbanized and connected to other rural areas and to major cities, their role in maintaining transmission and helping reseed epidemics is expected to increase [19,31]. In Esmeraldas, connectivity first increased with Colombia, consistent with the observation that the DENV serotypes circulating in Esmeraldas between 2010-2014 more closely matched those circulating in Colombia than the rest of Ecuador [17,19,29].…”
Section: Discussionmentioning
confidence: 69%
“…Aedes aegypti soon returned, followed by the re-introduction of dengue [3]. National dengue outbreaks occurred in Ecuador in 1996Ecuador in , 2000Ecuador in , 2005Ecuador in , 2010Ecuador in , 2012, and 2014 and since 2000, the four DENV serotypes have been detected in all regions [16,17]. A recent phylogenetic analysis showed both recent and historical introductions of DENV1 and DENV2 in Ecuador that originated from Venezuela and Colombia, while chikungunya was introduced through the Caribbean [18,19] Here, we modeled province-level age-stratified dengue prevalence data from 2000-2019 to estimate changes in the DENV transmission intensity for nearly 80 years and across provinces in Ecuador.…”
Section: Introductionmentioning
confidence: 99%